Codification of Arabic Verb Inflection: Easy Method to Understand the Basic of Words’ Formation for Indonesian Learners - Titin Nurhayati Mamun; Tanty Riyani (International Islamic Schools Alliance, 2018)
The abundance of words’ change in Arabic language has become a challenge for Indonesians to learn Arabic language. Almost every lingual unit in Arabic may change depending on the number, subject, or its position. These changes require Arabic language learners to memorize all examples of words’ form in order to use the language properly. One of the most common forms of word’s change in Arabic is in verbs. The verbs in Arabic are three kinds: madhi (past form), mudhori (present form), and amr (order form). The formation of verb form changes commonly called tashrif lughowy (inflection) is a common way of learning Arabic language. If an encoding process applied to Arabic verb inflection, it would create an easy method to understand the basic of word’s formation. This research used morpholinguistic theory in Arabic inflection codification process and used questionnaire to measure the effectiveness of easy method to understand the basic formation of Arabic word. The results of this study are: (1) Arabic verb inflection codification process; (2) Codification of Arabic verb inflection and its use; (3) Indonesian learner's response to an easy method to understand the basic formation of Arabic words.